Anthropogenic platinum group element (Pt, Pd, Rh) concentrations in PM10 and PM2.5 from Kolkata, India - Diong, Huey Ting (2017)
This study investigates platinum group elements (PGEs) in the breathable (PM10) and respirable (PM2.5) fractions of air particulates from a heavily polluted Indian metro city. The samples were collected from traffic junctions at the heart of the city and industrial sites in the suburbs during winter and monsoon seasons of 2013–2014. PGE concentrations were determined by inductively coupled plasma-mass spectrometry (ICP-MS). The PGE concentrations in the samples from traffic junctions are within the range of 2.7–111 ng/m3 for Pd, 0.86–12.3 ng/m3 for Pt and 0.09–3.13 ng/m3 for Rh, and from industrial sites are within the range of 3.12–32.3 ng/m3 for Pd, 0.73–7.39 ng/m3 for Pt and 0.1–0.69 ng/m3 for Rh. Pt concentrations were lower in the monsoon compared to winter while Pd concentrations increased during monsoon and Rh stayed relatively unaffected across seasons. For all seasons and locations, concentrations of Pd > Pt > Rh, indicating dominance of Pd-containing exhaust converters. Most of the PGEs were concentrated in the PM2.5 fraction. A strong correlation (R ≥ 0.62) between the PGEs from traffic junction indicates a common emission source viz. catalytic converters, whereas a moderate to weak correlation (R ≤ 0.5) from the industrial sites indicate mixing of different sources like coal, raw materials used in the factories and automobile. A wider range of Pt/Pd, Pt/Rh and Pd/Rh ratios measured in the traffic junction possibly hint towards varying proportions of PGEs used for catalyst productions in numerous rising and established car brands.